Rapid detection of Acinetobacter baumannii and molecular epidemiology of carbapenem-resistant A. baumannii in two comprehensive hospitals of Beijing, China - Li, Puyuan; Niu, Wen kai; Li, Huan; Lei, Hong; Liu, Wei; Zhao, Xiangna; Guo, Leijing; Zou, Dayang; Yuan, Xin; Liu, Huiying; Yuan, Jing; Bai, Changqing (Frontiers in Microbiology, 2015)
Acinetobacter baumannii is an important opportunistic pathogen associated with a variety of nosocomial infections. A rapid and sensitive molecular detection in clinical isolates is quite needed for the appropriate therapy and outbreak control of A. baumannii. Group 2 carbapenems have been considered the agents of choice for the treatment of multiple drug resistant A. baumannii. But the prevalence of carbapenem-resistant A. baumannii (CRAB) has been steadily increasing in recent years. Here, we developed a loop-mediated isothermal amplification (LAMP) assay for the rapid detection of A. baumannii in clinical samples by using high-specificity primers of the blaOXA-51 gene. Then we investigated the OXA-carbapenemases molecular epidemiology of A. baumannii isolates in 2 comprehensive hospitals in Beijing. The results showed that the LAMP assay could detect target DNA within 60 min at 65°C. The detection limit was 50 pg/μl, which was about 10-fold greater than that of PCR. Furthermore, this method could distinguish A. baumannii from the homologous A. nosocomialis and A. pittii. A total of 228 positive isolates were identified by this LAMP-based method for A. baumannii from 335 ICU patients with clinically suspected multi-resistant infections in 2 hospitals in Beijing. The rates of CRAB are on the rise and are slowly becoming a routine phenotype for A. baumannii. Among the CRABs, 92.3% harbored both the blaOXA-23 and blaOXA-51 genes. Thirty-three pulsotypes were identified by pulsed-field gel electrophoresis, and the majority belonged to clone C. In conclusion, the LAMP method developed for detecting A. baumannii was faster and simpler than conventional PCR and has great potential for both point-of-care testing and basic research. We further demonstrated a high distribution of class D carbapenemase-encoding genes, mainly OXA-23, which presents an emerging threat in hospitals in China.